The parallel economy in India: causes, impacts and governement initiatives - Sarkar, Sukanta (Economic Journal of Development Issues, 2012)
The study has made an attempt to assess the overall profile of parallel economy in India, particularly in terms of causes, impacts and government initiatives. The results indicate that parallel economy has been expanding very rapidly in India as well as in developing countries. It is evident from the study that government of India already introduced various commissions for estimating black economy but estimation reports are not same. Indian government is more concerned about the prevalence of the parallel economy and various commissions are formed for controlling it but results are not so impressive. Thus, the paper suggests that recommendations of the commissions or laws should be implemented correctly for reducing bad effects of black economy. Key words: Black money; Inflation; Privatization; Real estate; India Economic Journal of Development Issues Vol. 11 & 12 No. 1-2 (2010) Combined Issue Page: 124-134 Uploaded date: 10 April, 2012